TLR-4 Signaling vs. Immune Checkpoints, miRNAs Molecules, Cancer Stem Cells, and Wingless-Signaling Interplay in Glioblastoma Multiforme—Future Perspectives - Litak, Jakub (Int J Mol Sci, 2020)
Toll-like-receptor (TLR) family members were detected in the central nervous system (CNS). TLR occurrence was noticed and widely described in glioblastomamultiforme (GBM) cells. After ligand attachment, TLR-4 reorients domains and dimerizes, activates an intracellular cascade, and promotes further cytoplasmatic signaling. There is evidence pointing at a strong relation between TLR-4 signaling and micro ribonucleic acid (miRNA) expression. The TLR-4/miRNA interplay changes typical signaling and encourages them to be a target for modern immunotherapy. TLR-4 agonists initiate signaling and promote programmed death ligand-1 (PD-1L) expression. Most of those molecules are intensively expressed in the GBM microenvironment, resulting in the autocrine induction of regional immunosuppression. Another potential target for immunotreatment is connected with limited TLR-4 signaling that promotes Wnt/DKK-3/claudine-5 signaling, resulting in a limitation of GBM invasiveness. Interestingly, TLR-4 expression results in bordering proliferative trends in cancer stem cells (CSC) and GBM. All of these potential targets could bring new hope for patients suffering from this incurable disease. Clinical trials concerning TLR-4 signaling inhibition/promotion in many cancers are recruiting patients. There is still a lot to do in the field of GBM immunotherapy.